F x h fx 3 x 6xh 3h 4 x 4h 5 3 x 4 x

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: tient is to get the “h” or the " Δ x " in the denominator to cancel out. VI. Examples using f(x) = 3 x2 − 4x − 5 [see IV for the “f(x + h)” substitution] 2 2 2 A. f ( x + h) − f(x) = [3 x + 6xh + 3h − 4 x − 4h − 5] − (3 x − 4 x − 5) h h 3x 2 + 6xh + 3h2 − 4 x − 4h − 5 − 3 x 2 + 4x + 5 6xh + 3h2 − 4h = h h h (6 x + 3h − 4) = = 6x + 3h − 4 h = B. f( a + h) − f(a) = 6a + 3h − 4 h C. f ( 5 + h) − f(5) [3(5 + h)2 − 4(5 + h) − 5] − (3 i 52 − 4(5)...
View Full Document

This document was uploaded on 01/22/2014.

Ask a homework question - tutors are online